Variação da temperatura superficial dos músculos masseter e temporal anterior durante o apertamento dental voluntário com placas interoclusais maxilares de duas diferentes espessuras - Pita, Murillo Sucena; Ribeiro, Adriana Barbosa; Garcia, Alicio Rosalino [UNESP]; Pedrazzi, Vinicius; Zuim, Paulo Renato Junqueira [UNESP] (My University, 2013)
Muscle activity has been studied indirectly through analyses of temperature variation in skin surface temperature on the masticatory muscles. These procedure may be an important tool for clinical evaluation and assessment of the evolution of temporomandibular disorders, as well as monitoring the adopted protocol. Thus, its utilization for identified pathological alterations on blood circulation and/or on metabolic activity in subcutaneous tissues, such as the masticatory muscles, is justified. The aim of this study was to investigate the effect of occlusal splints’ thickness on the variation of surface temperature of the anterior temporal and masseter muscles during rest and clenching. It were analyzed 20 symptomatic subjects (10 males and 10 females) selected through the Research Diagnostic Criteria (RDC) questionnaire. Temperature expressed in degrees Celsius (ºC) was measured on the surface of both muscles measured with the aid of a digital thermometer with an infrared radiation reading system. The surface temperature of the anterior temporal and masseter muscles presented significant reduction during teeth clenching in relation to the mandibular rest position. However, there were no significant differences between conditions with and without occlusal splint or between the different thicknesses of splints analyzed. Masticatory muscles showed a considerable similar behavior for both sides, and no significant distinctions were observed between male and female patients.

A atividade muscular tem sido estudada de maneira indireta pela análise da variação da temperatura superficial cutânea sobre os músculos mastigatórios. Essas mensurações podem representar uma ferramenta valiosa na avaliação clínica da atividade e do progresso das desordens temporomandibulares, bem como no acompanhamento do protocolo terapêutico adotado, justificando sua utilização para verificar alterações patológicas na circulação sanguínea e/ou atividade metabólica nos tecidos abaixo da pele, como os músculos mastigatórios. Em vista disso, o objetivo do presente estudo foi verificar o efeito da espessura da placa interoclusal sobre a variação da temperatura superficial dos músculos temporal anterior e masseter, durante o repouso e o apertamento dental, considerando-se a condição assintomática de 20 indivíduos (10 do gênero masculino e 10 do gênero feminino) selecionados através do questionário Research Diagnostic Criteria (RDC). A temperatura em graus Celsius (ºC) da superfície dos músculos masseter e temporal anterior foi medida com o auxílio de um termômetro digital, com um sistema de leitura por irradiação infravermelha. A temperatura superficial dos músculos temporal anterior e masseter apresentou redução significativa diante do apertamento dental em relação à posição de repouso mandibular. Entretanto, não houve diferenças significantes entre as condições com e sem placa interoclusal, bem como entre as distintas espessuras de placas interoclusais analisadas. Adicionalmente, os músculos mastigatórios apresentaram uma considerável semelhança entre os lados, sem haver também distinções significantes entre o gênero masculino e o feminino.
Variation of surface temperature on superficial masseter and anterior temporal muscles during voluntary teeth clenching with maxillary splints of two different thicknesses
Keywords: Masseter muscle; Temporal muscle; Occlusal splints; Músculo masseter; Músculo temporal; Placas oclusais